2000
DOI: 10.1103/physreve.62.7478
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation-induced transport in a spatially symmetric periodic potential

Abstract: We present an analytical investigation of the fluctuation-induced transport of Brownian particles in a deterministic spatial symmetrical periodic potential subject to Gaussian noises. We found that directed motion of the Brownian particles can be induced by the correlation between a multiplicative white noise and an additive white noise. The direction of current is determined by the sign of the noise correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…[29] and is also similar to results obtained for the Langevin dynamics of Brownian particles in the asymmetric problems discussed in Sec. III C 2 [7,8,12,96]. We emphasize that whereas the resonance of this Brownian particle occurs in "noise rectifiers" with zero applied bias, we are instead discussing the effects of noise on a system with a nonzero average bias.…”
Section: Numericsmentioning
confidence: 99%
“…[29] and is also similar to results obtained for the Langevin dynamics of Brownian particles in the asymmetric problems discussed in Sec. III C 2 [7,8,12,96]. We emphasize that whereas the resonance of this Brownian particle occurs in "noise rectifiers" with zero applied bias, we are instead discussing the effects of noise on a system with a nonzero average bias.…”
Section: Numericsmentioning
confidence: 99%
“…In 1998, a noise-induced transport system with an asymmetric total noise composed of two correlated symmetric noise sources has been proposed by Li and Huang [7,8]. Recently the noise-induced transport in a spatially symmetric periodic potential with white correlation between the additive noise and the multiplicative noise are investigated by some researchers [9][10][11][12][13]. They showed that the correlation noises produce significant impact.…”
Section: Introductionmentioning
confidence: 97%
“…Also Madureira et al pointed out that fluctuations in some of the model parameters lead to noise contribution of both additive and multiplicative character, and are also not independent [27]. The effect of correlations between additive and multiplicative noise, either on a stationary state or on dynamics of the bistable potential system, have been widely studied [25,26,[28][29][30][31][32][33]. In the present paper we have studied a related issue.…”
mentioning
confidence: 94%
“…Since the interaction with non-thermal environment is relatively stronger than the thermal environment, multiplicative and additive noises in (2) are due to non-thermal and thermal environments respectively. We assume that the correlation time of the ζ(t) and η(t) are non-zero [31][32][33][34][35].…”
mentioning
confidence: 99%